Formative Assessment: Challenges and Strategies from English Teachers’ Perspective - Durratu Fakhria Nasution; Nida Husna (Universitas Islam Negeri Palopo, 2025)
The importance of formative assessment cannot be ignored. Daily assessment as a form of formative assessment is essential because they have a role as giving feedback mechanism and promote students’ advancement. This research used qualitative study to explore the various approaches and viewpoints from the teachers about the daily assessment they used in the English classroom. The participants of this research were 5 EFL teachers, 3 from elementary schools, and 2 from junior high school. The findings showed that most of the teachers use quiz and performance based for the daily assessment. Furthermore, the research also found that the teachers face some challenges in developing daily assessment in their classroom.